Equity and Efficiency in Public Sector Pricing: The Optimal Two-Part Tariff - Feldstein, Martin S. (Quarterly Journal of Economics, 1972)
I. Introduction, 175. — II. The optimal price, 176. — III. The welfare loss due to incorrect pricing, 182. — IV. An example, 183. — V. Concluding remarks, 187.